Kondisi Optimum Pemisahan Aseton dari Campuran Aseton-Etanol-Air-n–Butanol Dengan Kolom Distilasi Vacuum - Chairul Irawan; Iryanti Fatyasari Nata (INFO-TEKNIK, 2005)
Fermenting molasses using clostridium acetobutilycum can produce a mixture of acetone (1)/ethanol (2)/water (3)/n-butanol (4). The fermentation products are then separated and purified in a series of distillation column. In this work the products are 99.5-wt % of acetone and 99 % recovery.This work is primarily concerned with the effect of operating pressure on the distillation column performance. Distillation columns were designed using computer programs written in VISUAL FORTRAN 5.0. A rigorous equilibrium based computation method due to Wang-Henke that taking into account the effects of non-equal molar overflow and non-ideal vapor-liquid equilibrium was used in study. UNIQUAC, a method of estimating activity coefficient in non-ideal liquid mixtures, was used to model the vapor–liquid equilibrium. The column performance was studied by varying the operating pressure that is constrained by the cooling water temperature in the condenser. The numbers of plates are 50 and feed plate location at 12th plate below the condenser for acetone column. Variation of pressure 0.7 to 0.6 atm for acetone column will decrease 6.03 % reflux ratios, 4.3% condenser and 4.78% reboiler duty. Optimum condition for acetone column was 0.6 atm.